Comparison of pre-operative ultrasonography and magnetic resonance cholangiopancreatography with intra-operative surgical findings among patients suspicious to choledocholithiasis - Samanta, Pulak Kumar; Sarkar, Rathin; Bakshi, Sabyasachi (International Surgery Journal, 2020)
Background: Choledocholithiasis with cholelithiasis is a common problem in the middle and older age group people. Aim of this study is to assess the usefulness of ultrasonography in the diagnosis of choledocholithiasis in resource poor set up. Methods: After matching the inclusion and exclusion criteria, all cases of diagnosed choledocholithiasis were taken for this prospective, single center, observational study. Results: Out of total 130 subjects, 41 were male and 89 were female. Increased incidence of choledocholithiasis was found in females (M:F=1:2.08). The mean age of presentation was 49.27±10.60 years. Ultrasonography was able to diagnose common bile duct (CBD) stones in 57 patients (43.84%) and ductal dilatation in 89 (68.46%). Whereas, magnetic resonance cholangiopancreatography (MRCP) detected CBD stones in 112 (86.15%). Cholelithiasis was associated with choledocholithiasis in 108 patients (83.07%). Conclusions: In the evaluation of choledocholithiasis, in our study particularly trans-abdominal ultrasonography (USG) seemed to have a lower yield than expected for accuracy in determining choledocholithiasis when compared to MRCP and Intra-operative findings. So, a negative USG in a particular may not exclude choledocholithiasis. So, MRCP is the ‘investigation of choice’ among the suspicious patients for CBD stone disease. That is why prior to cholecystectomy in symptomatic patients with deranged liver function test, MRCP always to be done, to detect the missed stone in CBD.